(untitled) (International Journal of Culture and Art Studies, 2025)
This study explores the Gondang Mandudu ceremony, a sacred ancestral ritual in the Batak Toba community, specifically practiced to ward off the threat of COVID-19. Conducted by the Ruma Parsaktian Ompung Raja Isumbaon Community, this ceremony features the unique phenomenon of playing gondang sabangunan for approximately one hour, which is believed to invoke spiritual protection. This research aims to provide a descriptive account of the ceremony and understand its objectives in the context of the COVID-19 pandemic. Primary data was gathered through direct field research using a qualitative descriptive method, and secondary data from academic books and articles was added to the primary data. This triangulation-validated data ensured that the secondary sources and field observations were consistent. The findings highlight the significance of the ritual in the cultural and spiritual context of the community, showcasing its role in invoking protection from misfortune. This study contributes to the understanding of indigenous responses to global health challenges. It offers insights into the cultural significance of traditional rituals in modern times.